Injuries and illnesses in athletes with spinal cord injury during the 2012 London Summer Paralympic Games - Swart, Thomas Frederick (Division of Exercise Science and Sports Medicine, 2019)
Background: The Summer Paralympics have grown from participation of a mere 16 athletes at the 1948 Stoke-Mandeville Games, to a large multi-code event of 4176 athletes competing in 20 different sporting codes at the 2012 London Summer Paralympic Games. Unlike able-bodied athletes, Paralympic athletes represent a heterogenous group of people with a varied degree of physical-, mental- and physiological impairment. Despite the growth in the Paralympic sport, limited research exists describing injury and illness in Paralympic athletes. For athletes with impairment to perform optimally and not to jeopardise their health, studies should identify and eventually address risk factors for both injury and illness. Aim: The main aim of this study was to determine the incidence and nature of illnesses and injuries in a cohort of athletes with spinal cord injury (SCI) during the 3-day pre-competition and 11-day competition period at the 2012 London Summer Paralympic Games. This knowledge could provide an initial framework for future research regarding injury- and illness prevention strategies in athletes with SCI. Methods: This study was a component of the large prospective cohort study which was conducted over the 14-day period of the London 2012 Summer Paralympic Games, coordinated by the Medical Committee of the International Paralympic Committee (IPC). The data were collected at the London 2012 Summer Paralympic Games during the 3-day pre-competition and 11-day competition periods. Three data sources were used. Firstly, the IPC provided a comprehensive athlete database that contains accreditation number, country code, sports code (20 sports), gender and age. The second data source was the medical encounters of staff that provided care to their own teams. At the London 2012 Summer Paralympic Games, a novel system (WEB-IIS) was used to collect data via desktop computer interface, tablet or smart phone. The third data source was from an electronic medical data capture system (EMDCS) (ATOS, France) where the medical staff of the Local Organizing Committee of the London Summer Paralympic Games (LOCOG) were requested to enter all medical encounters, at both the Paralympic Village polyclinic and at the sports venues wherever the athlete reported for care. A standardized form was used for this purpose. After comparing all the data, a total of 3009 athletes, of which 709 were athletes with SCI formed part of this study. The Incidence Rate (IR) for illnesses and injuries in athletes with SCI was calculated as the number of illnesses and injuries per 1000 athlete days and was compared to a group of all other Paralympic athletes with injury and illness (who had other impairments). Results: There were significantly more upper limb injuries in athletes with SCI (p=0.0001), with an IR of 6.4 injuries / 1000 athlete days (95% CI 4.6 - 8.9). The IR for all the other athletes were 4.4 injuries / 1000 athlete days (95% CI 3.4 - 5.8). For lower limb injuries, the IR for athletes with SCI was significantly lower (p=0.0001) at 1.4 injuries / 1000 athlete days (95% CI 0.8 -2.5) compared to an average IR of 4.2 injuries / 1000 athlete days (95% CI 3.3-5.4) for all other athletes participating at the 2012 London Paralympic Games. Athletes with SCI had a significantly higher IR for illness than the group of all other athletes (p=0.0004). The IR for illness in athletes with SCI was 15.4 illnesses / 1000 athlete days (95% CI 11.8-20.1), whereas the average for all other athletes were 11.0 illnesses / 1000 athlete days (95% CI 8.7-14.1). The IR for skin- and genito-urinary illness were significantly greater in athletes with SCI (p=0.0001), with an IR of 3.9 illnesses / 1000 athlete days (95% CI 2.5-6.2) for skin illness and 2.3 /1000 athlete days (95% CI 1.8-4.6) for genito-urinary illness. The IR in skin illness for all other athletes were 1.8 illnesses / 1000 athlete days (95% CI 1.1-2.7) and genito-urinary illness, were 0.5 illnesses / 1000 athlete days (95% CI 0.3-0.8). Summary: The results of this study present an insight into injuries and illnesses in athletes with SCI. Athletes with SCI injury have a greater incidence rate of upper limb injuries and a lower incidence of lower limb injuries, than other Paralympic athletes. Total-, skin- and genito-urinary illnesses were also significantly greater in athletes with SCI compared to other Paralympic athletes. For clinicians caring for athletes with SCI, the results indicate that more attention should be given to the prevention of upper limb injuries and specifically skin- and genito-urinary illnesses.